2016
DOI: 10.1097/hjh.0000000000000941
|View full text |Cite
|
Sign up to set email alerts
|

Association of triglycerides and new lipid markers with the incidence of hypertension in a Spanish cohort

Abstract: : http://links.lww.com/HJH/A620.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 40 publications
6
81
3
Order By: Relevance
“…Although TG/HDLc is a useful surrogate of IR, it varies according to sex and ethnicity . The existing literature shows that TG/HDLc is associated with hypertension . However, in this study, we did not find that TG/HDLc was significantly associated with hypertension, even in subjects with elevated BMI.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Although TG/HDLc is a useful surrogate of IR, it varies according to sex and ethnicity . The existing literature shows that TG/HDLc is associated with hypertension . However, in this study, we did not find that TG/HDLc was significantly associated with hypertension, even in subjects with elevated BMI.…”
Section: Discussioncontrasting
confidence: 91%
“…27,28 The existing literature shows that TG/HDLc is associated with hypertension. 29,30 However, in this study, we did not find that TG/HDLc was significantly associated with hypertension, even in subjects with elevated BMI. The reason for the inconsistent results may be, on the one hand, the interethnic and sample size differences and, on the other hand, publication bias.…”
Section: Ir-compensatory Hyperinsulinemia Induces Carotid Body Overaccontrasting
confidence: 78%
“…Overall, this confirms that prediction of hypertension risk using METS‐IR could be explained by the increased cardiovascular risk associated with both IR and MS. Individual components of the METS‐IR score have also been linked independently to incident hypertension, including triglycerides and HDL‐C as well as BMI as a marker of whole‐body fat content . As demonstrated by our results, besides BMI, glucose levels are also highly predictive of arterial stiffness and incident arterial hypertension; despite this, the better model assessed by decreased in AIC was comprised by METS‐IR and not by its individual components.…”
Section: Discussionsupporting
confidence: 52%
“…Individual components of the METS-IR score have also been linked independently to incident hypertension, including triglycerides and HDL-C as well as BMI as a marker of whole-body fat content. 24,25 As demonstrated by our results, besides BMI, glucose levels are also highly predictive of arterial stiffness and incident arterial hypertension; despite this, the better model assessed by decreased in AIC was comprised by METS-IR and not by its individual components. This is significant, since it confirms that METS-IR is useful as a complementary metabolic evaluation tool when assessing risk of arterial hypertension.…”
Section: Discussionmentioning
confidence: 52%
“…Using the TG/HDL-C ratio in particular is a practical approach for identifying individuals who have insulin resistance [7, 8]. Several studies have also revealed that the TG/HDL-c ratio is more closely correlated with the incidence of hypertension [9], coronary heart disease [10], CVD [11] and albuminuria [12] than individual lipid profiles are. Meanwhile, non-HDL-c is calculated as TC minus HDL-c and includes all the atherogenic lipoproteins [13].…”
Section: Introductionmentioning
confidence: 99%